Feasibility study of ground palm oil fuel ash as partial cement replacement material in oil palm shell lightweight concrete / Mohammad Momeen Ul Islam - Mohammad Momeen, Ul Islam (2015)
The fresh concrete properties and mechanical properties of oil palm shell concrete (OPSC) containing palm oil fuel ash (POFA) as partial cement replacement have been evaluated. The effects of POFA replacement levels of 0%, 5%, 10%, 15%, 20% & 25% under different curing regimes, namely air curing, full water curing and initial water curing were investigated. For the evaluation of fresh concrete properties various test like slump, vebe second, compaction factor and wet density test were performed. The highest 28-day compressive strength of 42 MPa was obtained for the OPSC containing 10% of POFA under continuous water curing condition. The results also denoted cost reduction about 14% is possible for concrete produced from POFA based OPSC. Conversely, the splitting tensile and flexural strengths of OPSC decreased when increased amount of POFA was used. For durability properties, POFA was used as at 0%, 10%, 30% and 50% as replacement of ordinary Portland cement (OPC) when the water binder ratio (w/b) was 0.3 and again, OPC was replaced at 0% and 70% by POFA with w/b of 0.4.Different w/b was enacted to assess the outcome of pozzolanic reaction of POFA for different mixes. The durability tests include water absorption, sorptivity, drying shrinkage, sulphate attack and rapid chloride penetration test (RCPT) for 28- and 90-day water cured specimens. The water absorption and sorptivity values increase with the increase of POFA content. POFA based OPSC showed good resistance to sulphate attack. The drying shrinkage of POFA based concrete was higher with the increase of POFA content. The highest chloride ion penetration of about 5960 coulomb was recorded for the mix with 30% replacement of cement by POFA and with the further more replacement, the RCPT values were positively decreasing. In view of the current criteria for a sustainable environmental benefits, green building rating systems, infrastructure, the use of industrial wastes such as POFA and OPS as binder and coarse aggregates, respectively could benefit the concrete industry.